Numerical simulations as means for tailoring electrically conductive hydrogels towards cartilage tissue engineering by electrical stimulation - Zimmermann, Julius; Distler, Thomas; Boccaccini, Aldo R.; van Rienen, Ursula (Molecules, 2020)
Cartilage regeneration is a clinical challenge. In recent years, hydrogels have emerged as implantable scaffolds in cartilage tissue engineering. Similarly, electrical stimulation has been employed to improve matrix synthesis of cartilage cells, and thus to foster engineering and regeneration of cartilage tissue. The combination of hydrogels and electrical stimulation may pave the way for new clinical treatment of cartilage lesions. To find the optimal electric properties of hydrogels, theoretical considerations and corresponding numerical simulations are needed to identify well-suited initial parameters for experimental studies. We present the theoretical analysis of a hydrogel in a frequently used electrical stimulation device for cartilage regeneration and tissue engineering. By means of equivalent circuits, finite element analysis, and uncertainty quantification, we elucidate the influence of the geometric and dielectric properties of cell-seeded hydrogels on the capacitive-coupling electrical field stimulation. Moreover, we discuss the possibility of cellular organisation inside the hydrogel due to forces generated by the external electric field. The introduced methodology is easily reusable by other researchers and allows to directly develop novel electrical stimulation study designs. Thus, this study paves the way for the design of future experimental studies using electrically conductive hydrogels and electrical stimulation for tissue engineering.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Biomaterial scaffolds; Capacitive coupling; Computational modelling; Electrical stimulation; Electrically conductive hydrogels; Finite element analysis; Scaffold; Tissue engineering; Uncertainty quantification